The Axis Mundi and the Ritual Play: Displacement of immanent reality to achieve Hyerophani (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article proposes to analyze the scenic creation practices of the Arkhétypos Group in the light of the Ritual Game, relating it to the concept of axis mundi proposed by Mircea Eliade and the theories of the imaginary of Gilbert Durand.. We work with the hypothesis that the experience of myth manifested in the actor's body reorganizes the spatio-temporal relationship, allowing the public to displace the immanent reality so that hierophany can be achieved. In order to clarify the issue, we developed a brief reflection from the plays Santa Cruz do Não Sei (2011) and Revoada (2014) and we take a critical look at the colonization process suffered in the Americas.
Keywords: Axis Mundi; Ritual Play; Myth; Sacred Theatre; Imaginary